PERSEPSI MAHASISWA AKUNTANSI MENGENAI PENGARUH KEADILAN, SISTEM PERPAJAKAN, SANKSI PERPAJAKAN, DAN TRUST TO GOVERNMENT TERHADAP TINDAKAN PENGGELAPAN PAJAK (TAX EVASION) (Studi Pada Mahasiswa Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau & Mahasiswa Akuntansi Fakultas Ekonomi dan Ilmu Sosial Universitas Islam Negeri Sultan Syarif Kasim Riau) - Desni Irma Wika; Zirman Zirman; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aim to test Justice influence, System Taxation, Sanction Taxation, and Trust To Government To Action Tax Evasion. Population in this research is active Student of Strata One ( S1) Accountancy at College Country ( PTN) exist in Pekanbaru town. Used by Sampels type researcher is sampling purposive. Sampels in this research is Student Majors Accountancy generation 2014 taking taxation concentration at College Country ( PTN) town pekanbaru namely University Riau and University Islam Country Sultan Syarif Kasim Riau. Used Sampel in this research is 192 responder. The hypothesis tested by using doubled linear regresi analysis with SPSS version 17.This result indicate that Justice and System Taxation have an effect on significant to action Tax Evasion. While Sanction Taxation and Trust To Government do not have an effect on significant to action Tax Evasion. Level of independent variable influence to dependence variable pursuant to Adjusted R Square is equal to 25,2% while the rest 74,8% influenced by other variable which do not the included in this regresi model.Keyword : Justice, System Taxation, Sanction Taxation, and Trust To Government.